Teacher’s role in speaking acti Teacher’s role in speaking activities: Teacher’s role in speaking activities - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
The paper discusses different ways of improving learners’ speaking ability and teacher’s role in the process. The teacher’s influence in forming students’ speaking skill is inevitable which is presented in the paper